A new approach to quantify weed suppression, crop tolerance and weed‐free yield in cereal variety trials without weed‐free plots. (10th August 2021) - Rasmussen, Jesper; Jensen, Signe M.; Mariegaard Pedersen, Tove
Abstract: Cereal varieties are commonly tested in the presence of weeds in organic agriculture, and a variety of test programmes with weeds are relevant in relation to fields containing herbicide‐resistant weeds. However, the interpretation of results from variety trials with weeds is complex because different levels of weed pressure affect the yield differently. Crop yield is a result of the combined effect of weed suppression, crop tolerance and the weed‐free yield. Until now, there has been no attempt to separate weed suppression, crop tolerance and weed‐free yield in ordinary variety trials without weed‐free plots. This study applied a new approach based on the combination of functional trait analysis and analysis of variance (ANOVA). A total of 16 variety trials were analysed with early crop coverage, final canopy height and disease severity as functional traits. The main objectives were to quantify weed suppression, crop tolerance and weed‐free yield in spring barley varieties, and to evaluate the importance of the trade‐off between weed suppression and weed‐free yield. Results showed that early crop coverage and final canopy height both increased weed suppression, and taller cultivars tolerated weeds better than shorter cultivars. However, a trade‐off between canopy height and weed‐free yield made it difficult to justify the selection of tall varieties unless the weed pressure was at its maximum level in the trials. Large early crop coverage was an advantage in terms of weed suppression and weed‐free yield, making early coverage a better selection criterion than final canopy height under the condition that early coverage is a result of genotypic variation. Future studies have to show how well genotypic and phenotypic variations are related in terms of early coverage and final canopy height.